The Role of Leadership Style, Organizational Culture, and Work-Life Balance in Increasing Organizational Commitment in Millennial Employees - Nirvananda, Anandita; Endratno, Hermin; Widhiandono, Hengky; Innayah, Maulida Nurul (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of leadership style, organizational culture, and work-life balance on millennial employee organizational commitment using a purposive sampling approach to 115 respondents in Purwokerto. This research uses SEM-PLS analysis on the SmartPLS 4.0 application with Social Exchange Theory as the basis for the relationship approach between variables. The research findings show that the three independent variables, namely leadership style, organizational culture, and work-life balance, have a positive and significant effect on organizational commitment. With the Social Exchange Theory approach, these findings suggest that when organizations provide support through supportive leadership, positive work culture, and work-life balance, millennial employees will respond by increasing commitment to the organization.